J-like aggregation of a cationic polythiophene with hydrogen-bonding capabilities due to 1,4-dioxane: Solution excitation spectra and fluorescence, morphology and surface free energy of films - Domínguez Sergio E; Vuolle Antti; Butler-Hallissey Ciarán; Ääritalo Timo; Damlin Pia; Kvarnström Carita (Elsevier Inc., 2022)
This work presents solution- and solid-state evidence of the enhancement of J-like aggregation of a cationic polythiophene (CPT) with isothiouronium functionalities (PT1), caused by a decrease in the polarity and hydrogen-bonding (H-bonding) capacity of the solvent, generated by using a 50:50 v/v 1,4-dioxane-water mixture (W-DI) instead of water. In solution, the presence of 1,4-dioxane (DI) seems to generate selective solvation, tuning the energy transfer within PT1 from inter-chain into intra-chain, enhancing J-like aggregation. On the other hand, during the casting process, the presence of DI directs the interaction with solid-substrates, generating an increase in the solid-state fluorescence, modifying the morphology from one similar to ballistic-aggregation (BA) into one similar to attachment limited aggregation (ALA), DI also modifies the SFE by increasing slightly its polar contribution (γSp) and decreasing the dispersive one (γSd). These results can be explained to be caused by a "coating" effect in presence of DI (as proposed before experimentally and computationally). Our results show a clear correlation between the solution- and solid-state properties of PT1 in each solvent, further validating the use of the fluorescence excitation spectra to trace J-like aggregation of water-soluble conjugated polymeric fluorophores in solution. This information could be useful for predicting and designing specific mesoscopic architectures of CPTs (and conjugated polyelectrolytes in general), which are molecules lacking of clear structure-function guidelines for designing high-performance polythiophene-based interlayer materials, especially for CPTs (and conjugated polyelectrolytes (CPEs) in general), particularly those with H-bonding capabilities. To the best of our knowledge the use of solution-state fluorescence excitation spectra to identify J-like aggregation of water-soluble conjugated polymers (CPs) has been scarcely used/discussed in literature and no correlation with solid-state properties was reported previously.